Factors impacting successful salvage of the failing free flap. Issue 12 (26th August 2020) - Sweeny, Larissa; Curry, Joseph; Crawley, Meghan; Cave, Taylor; Stewart, Matthew; Luginbuhl, Adam; Heffelfinger, Ryan; Krein, Howard; Petrisor, Daniel; Bender‐Heine, Adam; Wax, Mark K.
Abstract: Background: Understanding factors impacting successful salvage of a compromised free flap. Methods: Multi‐institutional review of free flap reconstructions for head and neck defects (n = 1764). Results: Free flap compromise rate: 9% (n = 162); 46% salvaged (n = 74). Higher salvage rates in initial 48 hours (64%) vs after (30%; P < .001). Greater compromise (14%) and failure (8%) if inset challenging vs straightforward (6% compromise, 4% failure; P = .035). Greater compromise (23%) and failure (17%) following intraoperative anastomosis revision vs no revision (7% compromise, 4% failure; P < .0001). Success following arterial insufficiency was lower (60% failed, 40% salvaged) vs venous congestion (23% failed, 77% salvaged) ( P < .0001). Greater flap salvage following thrombectomy (66%) vs no thrombectomy (34%; P < .0001). Greater flap salvage if operative duration ≤8 hours (57%), vs >8 hours (40%) ( P = .04). Conclusions: There were higher rates of free flap salvage if the vascular compromise occurred within 48 hours, if due to venous congestion, if operative duration ≤8 hours, and if the anastomosis did not require intraoperative revision.